Knowledge, attitude and practices regarding no scalpel vasectomy in married men attending urban and rural health facilities in Maharashtra, India - Uplap, Pallavi A.; Malvi, Vaidehi (International Journal Of Community Medicine And Public Health, 2020)
Background: India will soon surpass China as the world’s most populous nation by 2022. Though India was the first to launch family planning in 1952, population stabilization remains a distant dream. No scalpel vasectomy (NSV) is a modified and sophisticated technique of vasectomy which can be performed in low resource settings. However, acceptance of NSV is declining in India including Maharashtra. Hence a study was conducted to evaluate factors affecting acceptance of NSV amongst married men visiting urban and rural health facilities of Maharashtra. Methods: A cross sectional study was conducted amongst randomly selected 50 married males of 21 years old and above each in conveniently selected urban and rural health centre under a medical college. After obtaining written informed consent from the participants, data was collected from November to December 2018 with the help of semi structured questionnaire. Socio-demographic information, knowledge, attitude and practices were entered and analyzed in Epi Info 7. Study was approved by the institutional ethics committee. Results: Majority (60%) of men attending the urban health care setup knew about NSV compared to those attending rural set up (34%). More number of participants from rural area (62%) were of opinion that NSV affects sexual performance as compared to urban area (44%). Willingness to recommend NSV to others was 62% and 32% in urban and rural men respectively. None of the participants (0%) underwent NSV. Conclusions: There is a huge gap between knowledge, attitude and practices regarding NSV in the study participants. It shows a need to revise strategies for its promotion.